Decentralization of DNS using Blockchain: A Survey - Ganai, Aabid Hussain; Sheheryar, Mir Aman (International Journal of Computer Sciences and Engineering, 2019)
the present DNS is a distributed network which helps in finding the IP addresses. The ICANN or the Internet Corporation for Assigned Names and Numbers lays the regulation for the functioning of DNS. It gives approval for the TLD or the Top Level Domain names like .com. It is the authority that accredit the registrars like the GoDaddy to sell the rights of using the domain name. The current DNS system is hierarchical. This system’s root servers represents a high-value attack vector. Since the entire system is centralized even the slightest failure at a single point can take down the whole internet. With a DNS of the Blockchain, it will be based on the decentralized system, and thus, it may not hamper the redirection process. Furthermore, Blockchain based DNS may counter the censure and also avoid the problem of cache poisoning or DNS spoofing. It is true that Blockchain-based DNS inherits the benefits of decentralization. Unlike the current DNS system which is governed and is controlled by organizations, Blockchain-based DNS does not have any authorities. Every node in the server is equal. Only the owners can make changes in the current records. It is difficult for the authorities to make any changes in the domain name records. The current DNS system is prone to attach and hacking, but this is not the case with Blockchain based DNS. Blockchain based DNS will host or store DNS records on blockchain in the form of blocks which means that every block will store domain name and its corresponding IP address (name, value pair).